Ethnobotanical survey in Canhane village, district of Massingir, Mozambique: medicinal plants and traditional knowledge - Tavares João; Romeiras Maria M; Ribeiro Ana; Faria Maria T (BMC, 2010)
Abstract Background Medicinal plants are used by 80% of people from developing countries to fulfill their primary health needs, occupying a key position on plant research and medicine. Taking into account that, besides their pharmaceutical importance, these plants contribute greatly to ecosystems' stability, a continuous documentation and preservation of traditional knowledge is a priority. The objective of this study was to organize a database of medicinal plants including their applications and associated procedures in Canhane village, district of Massingir, province of Gaza, Mozambique. Methods In order to gather information about indigenous medicinal plants and to maximize the collection of local knowledge, eleven informants were selected taking into account the dimension of the site and the fact that the vegetation presents a great homogeneity. The data were collected through intensive structured and semi-structured interviews performed during field research. Taxonomical identification of plant species was based on field observations and herbarium collections. Results A total of 53 plant species have been reported, which were used to treat 50 different human health problems. More than half of the species were used for stomach and intestine related disturbances (including major diseases such as diarrhea and dysentery). Additionally, four species with therapeutic applications were reported for the first time, whose potential can further be exploited. The great majority of the identified species was also associated with beliefs and myths and/or used as food. In general, the community was conscientious and motivated about conservational issues and has adopted measures for the rational use of medicinal plants. Conclusions The ethnomedicinal use of plant species was documented in the Canhane village. The local community had a rich ethnobotanical knowledge and adopted sound management conservation practices. The data compiled in this study show the social importance of the surveyed plants being a contribution to the documentation of PGR at the national and regional level.